Analisis Pengaruh Marketing Mix terhadap Keputusan Pemilihan PTS yang Dimediasi Variabel Brand Image (Studi pada Siswa SMAN di Kota Semarang) - Endang Kurniawati; Mohklas Mohklas (Prosiding Seminar Nasional Unimus, 2018)
The phenomenon that occurs in high school graduates and equivalent post graduation is always preoccupied with making choices in higher education. The priority that is his choice is to enter the State University. The reality that exists with various regulations from State Universities (PTN) is very competitive, which includes very minimal capacity. This condition causes Private Higher Education (PTS) to always increase the intensity of competition among higher education service providers. This causes demands to be able to implement the right marketing strategy by trying to offer higher education services that are in line with the expectations of prospective students (consumers). Universities need to consider the right marketing strategy in the right combination of marketing mix to win the competition. In general, this study aims to test, analyze the direct and indirect effects of marketing mix influence on the decision of private university selection with mediated brand image variables. So that it can be seen that the most dominant mediation pathway in influencing election decisions. Specifically this study aims to provide PTS management input advice in Semarang City, in improving the quality and quantity of performance in the marketing unit. The variables in this study consist of 6 (six) variables where in the first stage the variables of product, price, promotion, and location become independent variables while the decision to choose Private Higher Education becomes the dependent variable. Then in the second stage the fourth independent variable is mediated with the brand image variable. Data collection techniques were researched by distributing questionnaires to SMAN in Semarang City which were arranged systematically with several easy-to-understand answers. Distribution of questionnaires by being met directly in the middle of 2018, with a sample of 161 students. Then the data collected through the questionnaire is carried out by a data analyst test; validity and reliability, classical assumption test, path analysis followed by hypothesis testing.